2007
DOI: 10.1128/jb.00021-07
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Properties of Staphylococcus aureus and Bacillus Members of the Secondary Cation/Proton Antiporter-3 (Mrp) Family Are Revealed by an Optimized Assay in an Escherichia coli Host

Abstract: Monovalent cation proton antiporter-3 (Mrp) family antiporters are widely distributed and physiologically important in prokaryotes. Unlike other antiporters, they require six or seven hydrophobic gene products for full activity. Standard fluorescence-based assays of Mrp antiport in membrane vesicles from Escherichia coli transformants have not yielded strong enough signals for characterization of antiport kinetics. Here, an optimized assay protocol for vesicles of antiporter-deficient E. coli EP432 transforman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 71 publications
4
55
1
Order By: Relevance
“…Time-dependent DpH changes were monitored by measuring the quenching of acridine orange fluorescence using a Shimadzu-5300PC instrument (Shimadzu) with the excitation wavelength set at 492±1.5 nm and the emission wavelength set at 525±3.0 nm. Antiport activities were expressed as percentage fluorescence recovery of the total quenching values, as suggested by Swartz et al (2007) (Kiriyama et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Time-dependent DpH changes were monitored by measuring the quenching of acridine orange fluorescence using a Shimadzu-5300PC instrument (Shimadzu) with the excitation wavelength set at 492±1.5 nm and the emission wavelength set at 525±3.0 nm. Antiport activities were expressed as percentage fluorescence recovery of the total quenching values, as suggested by Swartz et al (2007) (Kiriyama et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…In bacteria, monovalent cation/H + antiporters are often considered to be major determinant factors for alkaline and Na + tolerance of cells (Padan et al, 1989(Padan et al, , 2005Putnoky et al, 1998). It has been shown that most of the cation/H + antiporters involved in alkaline tolerance are fully active in alkaline but inactive in neutral to acidic conditions, and such pH dependency is considered to be a critical feature for the maintenance of adequate intracellular pH (Taglicht et al, 1991;Swartz et al, 2007;Yamaguchi et al, 2009). Therefore, the molecular mechanism of the pH-dependent regulation of antiport activity has drawn particular attention for more than two decades (Padan, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…After the dequenching reached saturation, 25 mM ammonium chloride was added to dissipate remaining DpH in order to calculate the total quenching value. Antiport activities (dequenching) were expressed as a percentage of the total quenching value, as suggested by Swartz et al (2007). Activities of the Pha1 system were calculated by subtracting the values of TO114/pTrcHis2C vesicles from those of TO114/pTrcHis2C-pha1 under each condition.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the Mrp antiporters studied have been shown to be Na + /H + antiporters that play an important role in cytosolic pH homeostasis under alkaline conditions (Dzioba-Winogrodzki et al, 2009; Ito et al, 1999; Kosono et al, 1999;Swartz et al, 2007;Yang et al, 2006). The TO114/pTrcHis2C control strain showed almost no growth at pH 7.0, but the growth of the TO114/pTrcHis2C-pha1 strain in LBNa100 medium was significantly enhanced at pH values up to 8.5, but not at pH 9.0 (Fig.…”
Section: Functional Expression Of the Pha1 Complex In E Colimentioning
confidence: 99%
See 1 more Smart Citation